Urachal Tumor: A Case Report of an Extremely Rare Carcinoma. (22nd February 2017) - Palla Garcia, José; Sampaio, Rita; Peixoto, Carlos
Abstract : The urachus is a tubular structure that connects the bladder to the allantois in the embryonic development, involuting after the third trimester. The urachus carcinoma is an extremely rare tumor that accounts for <1% of all bladder cancers. We report a case of a 46-year-old woman, with no past medical history, complaining of hematuria with 6-month duration and a physical exam and an abdominal computed topographic scan revealing an exophytic mass of 6.8 cm longer axis that grew depending on the anterior bladder wall, invading the anterior abdominal wall. Cystoscopy detected mucosal erosion. The biopsy showed structures of adenocarcinoma of enteric type. The surgical specimen showed urachus adenocarcinoma of enteric type with stage IVA in the Sheldon system and stage III in the Mayo system. This case has a 3-year follow-up without disease recurrence.